Evaluation and comparison of inflammatory and insulin resistance indicators on recurrent cardiovascular events in patients undergoing percutaneous coronary intervention: a single center retrospective observational study - Ang Gao; Bo Peng; Yanan Gao; Zhiqiang Yang; Zhifan Li; Tingting Guo; Hong Qiu; Runlin Gao (Diabetology & Metabolic Syndrome)
Abstract Background The aim of this study was to evaluate and compare the usefulness of the C-reactive protein (CRP)-triglyceride glucose (TyG) index (CTI) and other insulin resistance (IR) or inflammatory indexes for predicting recurrent cardiovascular events in percutaneous coronary intervention (PCI)—treated patients. In addition, the mediating effects of systemic inflammation, represented by high-sensitive CRP (hs-CRP), on TyG index-associated adverse cardiovascular events across different subgroups were also evaluated. Methods The formula for calculating the CTI was 0.412 × ln [high-sensitivity CRP (mg/L)] + ln [triglyceride (mg/dl) × fasting glucose (mg/dl)/2]. The primary endpoint was defined as the incidence of major adverse cerebrovascular and cardiovascular events (MACCEs), including cardiovascular death, nonfatal acute myocardial infarction (AMI), nonfatal ischemic stroke and repeat coronary revascularization. Results Among the 2383 PCI-treated patients, 413 experienced MACCEs during a median of 34 months follow-up. Correlation analysis showed CTI was significantly associated with cardiometabolic factors. The CTI was the strongest predictor for MACCEs (adjusted HR 1.85, 95% CI 1.44–2.38) among the inflammatory and IR indicators. CTI had an incremental effect on the predictive ability of the prognostic model for MACCEs (NRI: 0.220, p < 0.001; IDI: 0.009, p < 0.001). Subgroup analysis revealed that the prognostic value of the CTI remained significant across all subgroups (all p < 0.05) whereas the predictive abilities of other IR or inflammatory indicators were more or less influenced by the metabolic abnormalities. Finally, mediation analysis revealed that the effects of systemic inflammation on TyG index—associated MACCEs were more prominent in patients with metabolic disorders. Conclusions CTI was a practical indicator for evaluating cardiometabolic diseases. Among the IR and inflammatory indicators, CTI was the most promising index for predicting recurrent cardiovascular risks in PCI-treated patients. TyG index—associated cardiovascular risks were partially mediated by systemic inflammation in patients with metabolic abnormalities.